EUTHANASIA DALAM PERSPEKTIF MORAL DAN HUKUM - Halim, Abdul (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
Euthanasia is a conduct which is done by a doctor or other persons. They do a certain medical conduct to end the patient life process, or do nothing to help the patient who severe some dieses according to medical science are difficult to be cared, either by the patient or family asking or not, in order to patient or family interest. In the ethics perspective, euthanasia face the very basic principle, even the patient condition is in the vegetative status. In the other side, in the positive law perspective, Indonesia has not yet regulate specifically in the euthanasia case, but in the formal juridic in the positive law, there in the only one euthanasia, namely the euthanasia which is conducted by asking from the patient or victim, what is called by voluntary euthanasia, according to act 344 KUHP. According to Islamic law, euthanasia is not allowed as well as in the positive law, because the right to live is not the human right but it‟s Allah rignt.